2019
DOI: 10.1155/2019/3161953
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on the Test Method for Tensile Elastic Modulus of Rock Materials

Abstract: Rock material has different mechanical behaviors under compressive and tensile loading. Correspondingly, there are two types of elastic modulus: compressive elastic modulus Ec and tensile elastic modulus Et, respectively. To distinguish which indirect test methodology, including three-points bending test and Brazilian disc test, is more suitable to measure the tensile elastic modulus Et of rock materials, a series of uniaxial compressive test (UCT), direct tensile test (DTT), three-points bending test, and Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In computational fracture models, however, the use of E C alone is invalid, as the elements in the cohesive zone can experience both tensile and compressive stress at varying times during crack growth. It has been demonstrated that elastic moduli of rock may differ considerably in compression versus tension (Zhang & Yu, 2019). We were unable to derive the E T of rock specimens from our experimental test efforts, so we utilized common sandstone values (~3.5 GPa) from the literature in G IC determinations, with the recognition that doing so introduced a layer of error into our analysis (Zhang & Yu, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In computational fracture models, however, the use of E C alone is invalid, as the elements in the cohesive zone can experience both tensile and compressive stress at varying times during crack growth. It has been demonstrated that elastic moduli of rock may differ considerably in compression versus tension (Zhang & Yu, 2019). We were unable to derive the E T of rock specimens from our experimental test efforts, so we utilized common sandstone values (~3.5 GPa) from the literature in G IC determinations, with the recognition that doing so introduced a layer of error into our analysis (Zhang & Yu, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…To determine the mechanical properties needed to predict rock fracture in our analog lithologies (Missoula mudstone and silt and sandstone of the Cutler, Clinch, and Chapman Ridge formations), three types of experimental testing were performed to characterize UCS, TS, and plane strain fracture toughness ( K IC ) (Figure 5). Compressive elastic modulus ( E C ) and fracture energy ( G IC ) were then derived via standard relationships (American Society for Testing and Materials (ASTM) 7012, 2014; Zhang & Yu, 2019) from UCS and K IC test results, respectively. Additional properties needed for computational model input included the tensile elastic modulus ( E T ) and Poisson's ratio ( v ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations